(untitled) (Bangladesh Medical Journal Khulna, 2021)
Background: Carcinoma cervix is a preventable disease. It runs a long preinvasive stage, such as Normal - CIN I - CIN II - CIN III - Cancer cervix. It can be prevented at early stage of development with proper diagnosis, treatment & follow up. A major portion of CIN I spontaneously regress but some need treatment. Obiective: The purpose of this study was to determine the frequency of abnormal colposcopic findings during the 1 year follow up period in patients of CIN I treated with cold coagulation, LEEP and expectant management. Materials and Methods: This retrospective study was conducted in colposcopic centre of Khulna medical college hospital, Khulna, Bangladesh from January 2018 to December 2019. After confirmation of CIN I, ladies were arranged in three groups according to their treatment modalities - Expectant management (group A), Cold coagulation (group B) & LEEP (group C). They were reexamined with colposcopy after 6 months, or after one year of first visit. Persistence or reappearance of CIN was assayed & correlation between colposcopic results during follow up of different groups was analysed. Results: Total 195 ladies were diagnosed colposcopically as CIN I. Of them 75 women were confirmed by histological examination. Among 75 ladies, 25 ladies received no treatment, grouped as group A. Forty ladies treated with cold coagulation falls in group B, whereas 10 ladies who treated with LEEP were grouped as group C. Distribution of age, parity, monthly income, education, marital age, age at first delivery was similar in different group. During follow up persistence of disease were found in 2(13.3%) ladies who did not receive any form of treatment, 3(10.7%) who were treated with cold coagulation (p value 0.333) and 1(12.5%) lady who received treatment with LEEP (p value 0.667), were not significant. Conclusion: Colposcopic surveillance without treatment appears reasonable in treating CIN I because of the high rate of spontaneous regression of CIN 1, but adherence to the follow up should be emphasized to the patients during the follow up visits. Bang Med J Khulna 2020: 53 : 8-12